Chronic tibial osteomyelitis in children. A case review at Hospital Tengku Ampuan Afzan, Kuantan - Awang, Mohd Shukrimi; Sharifudin, Mohd Ariff; Zakaria@Mohamad, Zamzuri; Taib, Mai Nurul Ashikin (Malaysian Medical Associations, 2015)
Osteomyelitis in children has various clinical manifestations causing diagnostic and therapeutic difficulties. Inappropriate treatment of acute osteomyelitis may lead to chronic, serious and complicated condition. Chronic osteomyelitis continues to be a major cause of morbidity and disability in children living in developing countries. We present three cases of tibial osteomyelitis that have different presentations and sequalae. Our intention is to alert our colleagues, particularly primary physicians, regarding the variety of presentation and the important of early diagnosis and treatment to reduce the risk of morbidity following osteomyelitis.